1451 Occupational exposure to pesticides among farmers: outcomes of survey and leads for prevention. (24th April 2018) - Moreau, Y; Lacauve, A-S; Deant, S; Tribouillard, V; Lévèque-Morlais, N; Perrier, S; Lailler, C; Faion, L; Lambert, V; Lecluse, Y; Apostolidis, T; Lebailly, P
Abstract : Introduction: Farmers are particularly exposed to pesticides while performing their professional tasks. In France, Certiphyto training program is aiming to decrease occupational exposure by improving knowledge. Several studies have shown the importance of the following two aspects, which are not taken into account by Certiphyto: psychosocial factors such as risks perceptions, peer norms, self-efficacy are important to better understand the underlying mechanisms of occupational exposure to pesticides among farmers; alternative educational strategies such as prevention by peers and practical exercises. Methods: We have conducted a national telephone survey among 197 farmers from three agricultural settings (open-field, open-field – cattle-breeding, viticulture) and we also realised an ergonomic and psychosocial analyse of Certiphyto by observation of sessions and semi-structured interview of trainers. Results: Direct exposure, studied by descriptive and comprehensive approach with determinants – frequency of Personal Protective Equipment (PPE) and adequacy with recommendations, hygiene habits, level of knowledge and psychosocial factors – is analysed in a comparative inter-setting perspective, indirect exposures, in an exploratory approach. Our results show that, among pesticide users, PPE use is weak but for gloves during preparation phase (60% of users use gloves systemically, 30% do not always use another PPE), and therefore insufficient according to recommendations. In addition, hygiene habits are also insufficient, both hygiene and PPE compliance being variable between agricultural settings. Similar observations have been made for indirect exposure. Analysis of psychosocial determinants highlights several obstacles for PPE use, among which discomfort of using PPE for specific task and peer norms. We also show persistence of inadequate habits and false knowledge after Certiphyto. Conclusion: We identified leads for the design of an alternative Certiphyto training including practical exercises and intervention of farmers peers. This prevention program, in design phase, will take into consideration psychosocial factors, specially risk perception, peer norms and health locus of control on developing psychosocial strategy.